Assessing alcohol use in situ: Correlates of self-report vs. objective alcohol consumption. (June 2022) - Cox, Melissa; Chaney, Beth; McDonald, Leah; Beth Miller, Mary
Highlights: Correlations between self-reported alcohol outcomes and BrAC are significant at low BrAC levels. Correlations between self-reported alcohol outcomes and BrAC are not significant at moderate and high BrAC levels. Intention to get drunk that night was associated with both self-report and objective measurement of alcohol use. Presence of peers one drinks with and witnessing others drunk predicted self-reported but not objective alcohol use. Abstract: Associations between self-report and objective measurement of young adult alcohol use are weakened by excessive consumption levels; therefore, associations between correlates of alcohol use and consumption likely also differ by alcohol measurement. This study examined the extent to which correlates of heavy drinking measured via self-report are also indicators of heavy drinking measured objectively. Data were collected from 164 bar patrons (54% male; 73% White, 12% Black, 15% Other; 15% Hispanic) as they exited the bar. Participants completed an intercept survey including self-reported measures of drinking, demographics, and social-environmental factors. A breath alcohol concentration (BrAC) reading was also obtained using a handheld breathalyzer device. Correlations between two self-reported outcomes, number of drinks consumed prior to and at the bar, and BrAC were significant among those in the lowest quartile of BrAC readings, but largely non-significant at moderate and high BrAC levels. Intention to get drunk that night was a robust predictor of alcohol consumption across self-reported outcomes and BrAC. Social factors (presence of drinking peers, witnessing drunk others) were predictive of self-reported alcohol use but not BrAC. AUDIT-C score was the only additional alcohol behavior predictive of objectively measured alcohol use. Self-reported outcomes and BrAC, as well as their association with key correlates, diverge at high levels of intoxication, when preventive intervention is most needed. Implications for further research and alcohol prevention practice are discussed.